Karakteristik Pembelajaran Sekolah Dasar: Kendala Dalam Mengimplementasikan Nilai Kearifan Lokal Di Sekolah Dasar - Annissabrina, Imelsi; Nasrul, Hikmah Setia; Ifliadi, Ilham; Abimanyu, Dwi Septian; MS, Agavin.; Joy Nebres , Arlene (Jurnal Gentala Pendidikan Dasar, 2023)
ABSTRACT _ This article aims to explore and analyze the obstacles that occur in implementing local wisdom values in elementary schools. The implementation of local wisdom values in elementary schools can serve as a reference, guideline, and direction for students in speaking, acting, and behaving in accordance with Indonesian society identity. The values contained in local wisdom can include religious values, tolerance, mutual cooperation, and care for the environment. Implementation of the values contained in local wisdom can be implemented through a number of positive activities that lead the character formation of students in a better direction. The obstacles in implementing local wisdom values can come from internal factors such as inner discouragement and demotivation, and external factors such as an inadequate environment. This article uses qualitative research with a descriptive approach. The data collection techniques used in this research were field observations and interviews.